ACCOUNTING PRINCIPLES UNDERLYING CORPORATE FINANCIAL STATEMENTS. A SYMPOSIUM. - Kohler, E. L. (The Accounting Review, 1942)
Abstract The article focuses on a symposium on various accounting principles underlying corporate financial statement. Those who have been charged with responsibility for activities of the American Accounting Association and its predecessor during the last 15 years frequently have occasion to recall the annual meeting held six years ago. For nearly ten years various members had proposed a restatement of aims and purposes of the association: a broadening of its expressed scope to cover the range of activities in which it seemed actually to be engaging and a more direct participation in practical affairs where national associations up to that date had seemed to be devices for the protection and defense of members, rather than mediums for the clarification and expansion of their fields of endeavor. Among other things, the devising of unequivocal statements of professional principles and policies had been suggested as a major project, notwithstanding that the normal interests of the association had been variously described as belonging to the realm of theory, pure science and academic narrowness.